Каховське водосховище: історія створення та наслідки - Бажан, О. (Краєзнавство, 2023)
У статті розглядаються проблеми спорудження Каховської гідроелектростанції, заходи по підготовці ложа майбутнього водосховища до затоплення. У фокусі уваги проєктно-вишукувальні роботи, реалізація заходів по переселенню жителів та переносу будівель із зони затоплення, інженерного захисту та санітарного очищення затопленої території. З’ясовано, що проєкт Каховського гідровузла не враховував питання впливу гідробудівництва на екологію Півдня України, прийняті владними структурами рішення про будівництво гідровузла не містили оцінки збитків від руйнування пам’ятників історико-культурної спадщини. The article deals with the problems of construction of the Kakhovka hydroelectric power station, measures to prepare the basis for flooding into the future reservoir. The focus of attention is put on project and research work, implementation of measures to resettle residents and transfer buildings from the flood zone, engineering protection and sanitary cleaning of the flooded territory. It is found that the impact of hydraulic engineering on the ecology of Southern Ukraine was not taken into account in the project of the Kakhovka hydroelectric station. In addition, an assessment of damages from the destruction of historical and cultural heritage monuments was not included in the decisions taken by the authorities on the construction of the hydroelectric station.